(3MGTjI GdTQGfTj aj GdGSJYGQIs - (3GdTQGfTjs ((3GHf YHO Gddg Ydi s)
(3ChdgG (B:s
(3bhdg Edi CdWGa QHg GdNajI LeY dWa s
(3BNQgG (B:s
(3JhTjM Ci ai GdecfjI hJLQjO ai GdeUQMI s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeOQSI GdCMeOjI (B_ (3GdehUd (B(256/1) s
Keywords: (3GdHdGZIs